1981
DOI: 10.1177/109719638100500201
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Thermal Inertia of Building Structures On Comfort and Energy Consumption

Abstract: A theoretical analysis was carried out in order to study the influence of the thermal inertia of building struc tures on thermal comfort and energy consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…The fundamental benefit of fabric's thermal mass is its ability to capture the internal, casual and solar heat gains, helping to moderate internal temperature swings and shifting the time that the peak load occurs [12,17,19,25,26]. Previous studies have also shown that the thermal mass of the fabric can be used to prevent buildings from overheating [23,27,28].…”
Section: Thermal Mass and Icfmentioning
confidence: 99%
“…The fundamental benefit of fabric's thermal mass is its ability to capture the internal, casual and solar heat gains, helping to moderate internal temperature swings and shifting the time that the peak load occurs [12,17,19,25,26]. Previous studies have also shown that the thermal mass of the fabric can be used to prevent buildings from overheating [23,27,28].…”
Section: Thermal Mass and Icfmentioning
confidence: 99%
“…This type of study analyzes what is usually known as urban building configurations or urban design, which consists of a group of buildings of different sizes grouped in such a way that the influence of factors such as wind velocity, solar radiation, among others, on the thermal performance of the built environment are studied. This type of studies have been carried out by authors such as Guglielmini et al (1981), Gao et al (2008), and Yasa (2017). Kahsay et al (2019) mentioned the importance of an accurate CHTC in thermal analysis in buildings, because this variable can generate an error between 20% and 40% when estimating buildings energy consumption.…”
Section: Studies On Urban Designmentioning
confidence: 99%
“…A building with an increased amount of thermal 2 of 13 mass is able to time-shift and flatten out heat flow fluctuations [9,10]; this is referred to as the thermal inertia of a building [8]. Guglielmini et al [11] introduce the term "passive thermoregulation effect" to describe the effect with which a building's thermal inertia is able to reduce the fluctuations of the inside air temperature.…”
Section: Introductionmentioning
confidence: 99%